2020
DOI: 10.1093/cid/ciaa1318
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sofosbuvir/Velpatasvir/Voxilaprevir for Hepatitis C Virus (HCV) NS5A-Inhibitor Experienced Patients With Difficult to Cure Characteristics

Abstract: Background In clinical trials, HCV salvage treatment with Sofosbuvir/Velpatasvir/Voxilaprevir (SOF/VEL/VOX) achieved an SVR12 rate of >95% in NS5A-experienced participants. Lower SVR12 rates have been reported in real-world studies, particularly for genotype (GT)3 infection and cirrhosis. We determined the efficacy and safety of SOF/VEL/VOX in a large real-world cohort. Methods We assessed the efficacy of salvage SOF/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 19 publications
3
50
0
Order By: Relevance
“…This is consistent with the data from Llaneras et al, 13 which also showed a SVR rate of 81% for GT3‐infected patients and 69% for GT3‐infected patients with cirrhosis. However, Papaluca et al 19 have shown an SVR rate of 90% in GT3 infected patients with cirrhosis. Belperio et al 11 have shown that GT1‐infected patients with prior SOF/VEL exposure had a reduced SVR rate of 79% (15/19), yet a GT3‐infected group with prior SOF/VEL exposure had a SVR rate of 85% (11/13) which is greater than the 75%(12/16) that was observed in our study but, these numbers remain small.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with the data from Llaneras et al, 13 which also showed a SVR rate of 81% for GT3‐infected patients and 69% for GT3‐infected patients with cirrhosis. However, Papaluca et al 19 have shown an SVR rate of 90% in GT3 infected patients with cirrhosis. Belperio et al 11 have shown that GT1‐infected patients with prior SOF/VEL exposure had a reduced SVR rate of 79% (15/19), yet a GT3‐infected group with prior SOF/VEL exposure had a SVR rate of 85% (11/13) which is greater than the 75%(12/16) that was observed in our study but, these numbers remain small.…”
Section: Discussionmentioning
confidence: 96%
“…31 Retreatment of patients without 59 In the real-world experience with VOX/VEL/SOF, with and without ribavirin, SVR rates of between 91-96% were reported following rescue treatment in cohorts from different countries. [60][61][62][63][64][65][66][67] Although the different studies are highly heterogeneous with respect to distribution of HCV genotypes and rate of patients with cirrhosis, based on larger numbers of patients it seems that HCV genotype 3a and cirrhosis are weak negative predictors of response, with SVR rates of 81-92% and 81-90%, respectively. Also, pretreatment with VEL/SOF was associated with lower SVR rates in some studies, while this was not observed in others (Table 3).…”
Section: Retreatment With Vox/vel/sofmentioning
confidence: 99%
“…Finally, it was also shown that in patients with endstage renal disease, as well as those with decompensated cirrhosis, administration of sofosbuvir and voxilaprevir, respectively, was safe. 63,68 Due to the potential liver toxicity of PIs in patients with decompensated cirrhosis, a lead-in phase with SOF plus a NS5A inhibitor may be considered to downstage patients to Child-Pugh class A cirrhosis before starting VOX/VEL/SOF. 63 Patients with failure on G/P were not enrolled in the VOX/VEL/SOF approval study.…”
Section: Retreatment With Vox/vel/sofmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Similarly, other real-world SOF/VEL/VOX retreatment outcomes and viral resistance analysis for HCV patients with prior failure to DAA therapy showed that GT3 infection (52/64; SVR = 81%, P = .009) and cirrhosis (47/58; SVR = 81%, P = .01) were both significantly associated with treatment outcome, 8,26 or showed lower SVR12 rate in NS5A-inhibitor experienced participants irrespective of difficult to cure characteristics including cirrhosis, portal hypertension or prior liver transplantation with GT3 infection 89% (59/66) vs 100% GT1a infection (n = 18/18), or 50% GT1b (n = 2/4) and 100% (n = 3/3) for GT6. 39 Overall, in our study we analysed 135 GT3-infected patients failing an interferon-free regimen. In particular, 85.2% failed a regimen recommended in the European 2017 guidelines, while 14.8%…”
Section: Discussionmentioning
confidence: 99%